New records of Porcellanola László, Ronkay & Witt, 2006 (Lepidoptera, Nolidae, Nolinae) from China, with description of a new species - Hu, Yanqing; Wang, Min; Han, Huilin (Zootaxa, 2014)
Materials Examined. Holotype. Male, Gaofeng, Lufeng, Yunnan, 2,230 m, 4.VIII.2013, Min Wang, Hailing Zhuang & Yu Wang (SCAU). Paratypes. 3 males & 1 female, Gaofeng, Lufeng, Yunnan, 2,230 m, 5.VIII.2013, Min Wang, Hailing Zhuang & Yu Wang (SCAU); 1 male, Midu, Yunnan, 2,340 m, 27.VII.2013, Min Wang, Hailing Zhuang & Zhenfu Huang (SCAU); 1 male, Jiangcheng, Yunnan, 15–17.IX.2008, Huilin Han & Mujie Qi (NEFU). The type specimens are deposited in the collection of South China Agricultural University, Guangzhou, China (SCAU) and Northeast Forestry University, Harbin, China (NEFU).